1986
DOI: 10.1172/jci112302
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein kinases in stimulation of human polymorphonuclear leukocyte oxidative metabolism by various agonists. Differential effects of a novel protein kinase inhibitor.

Abstract: Isoquinoline sulfonamides have recently been shown to exert novel inhibitory effects on mammalian protein kinases by competitively binding to the ATP substrate site (Hidaka, H., M. Inagaki, S. Kawamoto, and Y. Sasaki, 1984, Biochemistry, 23: 5036-5041). We synthesized a unique analog of the previously reported compounds, 145-isoquinolinesulfonyl) piperazine (C-I), in order to assess the role of protein kinases in modulating the agonist-stimulated oxidative burst of human polymorphonuclear leukocytes (PMN).Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1

Year Published

1986
1986
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(58 citation statements)
references
References 31 publications
3
54
1
Order By: Relevance
“…All of the reported agonist and antagonist properties of PMA have been shown to be inhibited by protein kinase C inhibitors [23,26,27]. There are two possible explanations for this result.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…All of the reported agonist and antagonist properties of PMA have been shown to be inhibited by protein kinase C inhibitors [23,26,27]. There are two possible explanations for this result.…”
Section: Methodsmentioning
confidence: 93%
“…In fact, a small but significant increase is commonly observed. Gerard et al [26] have very recently demonstrated that the stimulation by PMA of the oxidative metabolism of human neutrophils, but not by fMet-Leu-Phe, could be inhibited by an …”
Section: Methodsmentioning
confidence: 99%
“…However, the inhibitors which were used are known not to be specific for protein kinase C. Cl affects both protein kinase C and the cyclic AMP-dependent kinase, the K; for the former enzyme being-20 tM and for the latter, 3 tiM (Gerard et al, 1986) and the respective Ki values for H7 are 6 JAM and 3 JAM (Hidaka et al, 1984). The cyclic AMP-dependent kinase is known to inhibit neutrophil responses (Fantone & Kinnes, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…inhibitors were reported to inhibit PMA-but not receptor mediated 02 -formation, suggesting that NADPH oxidase activation by FMLP may be independent of PKC [4,5]. Furthermore, PKC-independent activation of NADPH oxidase in cellfree systems was demonstrated by us and others [6,7].…”
mentioning
confidence: 94%